Vidimo se u čitulji . The Crime that Changed Serbia - Baljak, Janko (Radio Free B92 ; ANEM, 1995)
This short but powerful documentary is concerned with a soaring crime in Serbia during the early 1990s. Made up of interviews with genuine criminals and gang members, showing uncensored photographs where they are fully equipped with guns, this documentary has a strong ring of authenticity to it. Set against the background of poverty and uncertainty in ex-Yugoslavia where especially the young could easily be tempted by the money and glamour of the criminal milieu, this is a real-life story about the generation whose idols were not pop stars, but rather notorious criminals such as Arkan. Desperately trying to appear as tough as they can, these young gangsters do not hesitate to brag openly about their misdeeds, assess the positive and negative aspects of their “profession” or explain the order of the day within the world of Belgrade crime. Almost all of the leading actors of the movie are dead by now, some of them did not even live to see the film itself finished. In fact, the film concludes with shots from the funeral of three men who appeared in the film, but were killed in gang clashes soon afterwards.